Role of QuantiFERON TB gold test for diagnosis of tuberculosis infection in prosthetic knee joint: a case report - Norliyana M; Nor Hamdan Mohamad Yahaya; Rizal Abd Rani (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Mycobacterium tuberculosis (MTB) is a rare cause of prosthetic joint infection. The diagnosis is challenging especially in cases of latent tuberculosis. QuantiFERON-TB Gold (QFT®) is an interferon-gamma relative assay (IGRA) which is highly specific and sensitive for detection of MTB infection. We report a case of 76-year-old lady diagnosed with tuberculous prosthetic joint infection following total knee replacement. Histological examination of abnormal synovial tissue taken intraoperatively reveals chronic granulomatous lesion and raised suspicion of tuberculous infection in otherwise asymptomatic patient. The tuberculin skin test, MTB acid-fast stain and tuberculosis polymerase chain reaction were negative. The diagnosis dilemma was solved with positive result of QuantiFERON TB Gold Test. The patient was treated with anti-tuberculous drug without any surgical intervention. At five months follow-up, patient was clinically well with no symptoms and signs of infection.